Transients in Electrical Systems: Analysis, Recognition, and Mitigation - Das J.C (Mc Graw Hill Higher Education, 2010)
his practical guide explains how to identify the origin of disturbances in electrical systems and analyze them for effective mitigation and control. Transients in Electrical Systems considers all transient frequencies, ranging from 0.1 Hz to 50 MHz, and discusses transmission line and cable modeling as well as frequency dependent behavior. Results of EMTP simulations, solved examples, and detailed equations are included in this comprehensive resource.